Lung transplant patients with coronary artery disease rarely die of cardiac causes. Issue 9 (30th August 2018) - Makey, Ian A.; Sui, Jin W.; Huynh, Charles; Das, Nitin A.; Thomas, Mathew; Johnson, Scott
Abstract: Background: A relative contraindication for lung transplant (LT) is coronary disease burden sufficient to cause risk of myocardial infarction after LT. We analyzed cause of death and outcomes of our LT patients with coronary artery disease (CAD). Methods: Inpatient records from March 1, 2004, to January 31, 2015, were retrospectively examined and data of 306 LTs extracted. Twenty‐five patients without coronary angiography (CA) and 7 with redo LTs were excluded. The other 274 patients were divided into 2 groups: CAD (n = 116) and no CAD (n = 158). Patients with prior revascularization or coronary stenosis >10% were placed into the CAD group. Results: The CAD group was older and had more male patients, greater history of smoking and hypertension, and greater proportion of patients with interstitial lung disease than the no‐CAD group. CAD patients were more likely to receive a single‐lung transplant. Death of cardiac causes occurred for 2 patients (1.7%) in the CAD group and for 1 patient (0.6%) in the no‐CAD group ( P  =   0.39). Conclusions: This analysis shows that compared with patients who have no CAD, patients with CAD have different demographic characteristics and receive more single‐lung transplants. Incidence of death of cardiac causes is rare.